Copernicus knowledge and innovation hubs - Riedler, Barbara; Lang, Stefan Christian; Zeil, Peter; Miguel-Lago, Mónica; Schröder, Christoph; Politi-Stergiou, Nefeli Vassiliki; Kerschbaumer, M.; Tramutoli, Valerio; Tzouvaras, Marios (My University, 2020)
Copernicus, the European Space program ensures free data availability and the organisational and financial framework to provide standardized information products in its service domains atmosphere, marine, land monitoring, climate change, emergency management and human security. A key to success to the market uptake process is knowledge exchange among all actors from the various sectors involved, notably research and educational institutions, industry, and the public sector. As a successful instrument to foster and stimulate this exchange, maximize the impact and additionally boost related capacity building and training activities, the Copernicus Academy has been anchored in the European Space Strategy. The present paper highlights some key activities to leverage the potential of this dynamically growing network of experts from universities and research institutions, public and private organizations, companies, stakeholders, and increase the benefit to its members. The vision of establishing both physical implementations of regional Copernicus hubs and virtual Copernicus hubs, built on key elements of the European Innovation strategy, is discussed. Regional hubs, attached e.g. to centres of excellence, are essential to meet local needs for exchange and training to boost the user uptake. The increasing importance of virtual hubs is becoming evident as a critical means to maximise synergies among actors in the rapidly advancing technological areas. Proposed technical elements demonstrate innovative solutions to visualize and facilitate easy harvesting of the Copernicus Academy membeŕs expertise for different stakeholder and the public, and show cast possibilities of active involvement and exchange within the network.
Keywords: Copernicus Academy; Copernicus services; CopHub.AC; Digital hubs; Innovation monitor; Knowledge landscape; Skills programme